Pengaruh Digital Guerilla Marketing Terhadap Brand Awareness By.U (Survei terhadap Followers Instagram @Byu.Id) - Lika Pitaloka; Tetty Herawaty; Arianis Chan (Master of Management Diponegoro University, 2022)
To increase and spread awareness in the marketing process there are various things that can be done one of them by using a guerrilla marketing approach through digital media or commonly known as digital guerilla marketing to spread awareness and increase engagement on social media. This research aims to find out the influence of digital guerilla marketing on brand awareness on #SultanMahbyUbas campaigns on Instagram followers @byu.id. The research method used is verifiable descriptive analysis with survey design. The population of the study is Instagram by followers. You by criteria have seen or known information about the campaign by. U with the theme '#SultanMahbyUbas' conducted by by.U. This survey was conducted to 100 respondents using non probability sampling using purposive sampling. The results of this study state that there is a positive and significant influence of digital guerilla marketing on brand awareness.